Are Married Spouses Insured by their Partners Social Insurance? - Martin Olsson; Peter Skogman Thoursie (Research Institute of Industrial Economics (IFN), 2011)
We use a Swedish sickness insurance reform to show that among married couples a partners benefit level affects spousal labour supply. The spousal elasticity of sick days with respect to the partners benefit is estimated to be 0.4, which is about one-fourth of the own labor supply elasticity. It is argued the main part of this effect is an insurance income effect.
Keywords: D10; J13; J22; 330; Spousal labor supply; Spill-over; Social insurance programs; Sozialversicherung; Versicherungsschutz; Ehe; Arbeitsangebot; Spillover-Effekt; Schweden